2014
DOI: 10.1021/jp507571u
|View full text |Cite
|
Sign up to set email alerts
|

Role of Internal Water on Protein Thermal Stability: The Case of Homologous G Domains

Abstract: In this work we address the question whether the enhanced stability of thermophilic proteins has a direct connection with internal hydration. Our model systems are two homologues G-domains of different stability: the mesophilic G domain of the Elongation-Factor thermal unstable protein from E. coli and the hyperthermophilic G domain of the EF-α protein from S. solfataricus. Using molecular dynamics simulation at the microsecond time-scale we show that both proteins host water molecules in internal cavities and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 89 publications
(263 reference statements)
3
38
0
Order By: Relevance
“…The internal hydration was found to contribute to the stability gap between the two homologues. A gain of about 1.3-2.5 kcal/mol was estimated in favour of the hyperthermophilic domain that corresponds to the shift of melting temperature of about 6 K, almost 16 of the experimental shift between the two proteins20. It was also clearly shown that internal hydration correlates to the flexibility/rigidity of the protein matrix20,53.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…The internal hydration was found to contribute to the stability gap between the two homologues. A gain of about 1.3-2.5 kcal/mol was estimated in favour of the hyperthermophilic domain that corresponds to the shift of melting temperature of about 6 K, almost 16 of the experimental shift between the two proteins20. It was also clearly shown that internal hydration correlates to the flexibility/rigidity of the protein matrix20,53.…”
Section: Introductionmentioning
confidence: 77%
“…They pointed out that at high temperature dewetting of the internal cavities leads to denaturation. Recently, some of our group members performed a comparative study between a mesophilic and hyperthermophilic G-domains20,25,52,53. The internal hydration was found to contribute to the stability gap between the two homologues.…”
Section: Introductionmentioning
confidence: 99%
“…This offers an explanation for the existence of internal water molecules in thermostable proteins proposed recently. 23,24,50,51 The mode of interaction of the ion pair is via head-to-head interaction of the oppositely charged ion pair, and the association of the ion pair is a balance between direct ion-ion interactions and the extent of solvation of the ions. Furthermore, the desolvation penalty associated with the formation of the ion pairs decreases with an increase in temperature, and, consequently, the stabilization due to the association of the ions is more significant at higher temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…23 25 However, at high temperatures, thermostable proteins lose some of these coordinating water molecules, implying that interactions between residues are more direct. 18,23 The effect of ion pair and hydrophobic interactions on the stability of a protein has been investigated by employing small model systems that resemble the naturally occurring amino acids. 26 36 These model systems can accurately capture electrostatic/hydrophobic interactions between amino acids while at the same time reducing the computational complexity.…”
Section: Introductionmentioning
confidence: 99%
“…Water molecules work as a lubricant to facilitate protein dynamics [ 104 ], yet serve as glue in binding interfaces [ 113 ], leading to conclusions that protein function is critically coupled to hydration [ 43 , 57 , 123 ]. Generally, dehydration of amino acid residues or loss of the hydration layer in proteins results in loss of activity and flexibility [ 78 ], while internal hydration of proteins is correlated with its conformational space [ 124 , 125 ]. Water molecules located at interfacial regions and in the active site, identified in crystallographic structures, often play structural and functional roles [ 61 ].…”
Section: Effect Of Small Molecule Interactions On Protein Structurmentioning
confidence: 99%